Phase I/II Study of Safety and Preliminary Efficacy of Intravenous Allogeneic Mesenchymal Stem Cells in Chronic Stroke - Levy, Michael L; Crawford, John R; Dib, Nabil; Verkh, Lev; Tankovich, Nikolai; Cramer, Steven C (Stroke (1970), 2019)
Background and Purpose- Stroke is a leading cause of long-term disability. Limited treatment options exist for patients with chronic stroke and substantial functional deficits. The current study examined safety and preliminary efficacy estimates of intravenous allogeneic mesenchymal stem cells in this population. Methods- Entry criteria included ischemic stroke >6 months prior and substantial impairment (National Institutes of Health Stroke Scale score ≥6) and disability. Enrollees received a single intravenous dose of allogeneic ischemia-tolerant mesenchymal stem cells. Phase 1 used a dose-escalation design (3 tiers, n=5 each). Phase 2 was an expanded safety cohort. The primary end point was safety over 1-year. Secondary end points examined behavioral change. Results- In phase 1 (n=15), each dose (0.5, 1.0, and 1.5 million cells/kg body weight) was found safe, so phase 2 subjects (n=21) received 1.5 million cells/kg. At baseline, subjects (n=36) averaged 4.2±4.6 years poststroke, age 61.1±10.8 years, National Institutes of Health Stroke Scale score 8 (6.5-10), and Barthel Index 65±29. Two were lost to follow-up, one was withdrawn and 2 died (unrelated to study treatment). Of 15 serious adverse events, none was possibly or probably related to study treatment. Two mild adverse events were possibly related to study treatment, a urinary tract infection and intravenous site irritation. Treatment was safe based on serial exams, electrocardiograms, laboratory tests, and computed tomography scans of chest/abdomen/pelvis. All behavioral end points showed significant gains over the 12-months of follow-up. For example, Barthel Index scores increased by 6.8±11.4 points (mean±SD) at 6-months ( =0.002) and by 10.8±15.5 points at 12-months ( <0.001) post-infusion; the proportion of patients achieving excellent functional outcome (Barthel score ≥95) increased from 11.4% at baseline to 27.3% at 6-months and to 35.5% at 12-months. Conclusions- Intravenous transfusion of allogeneic ischemia-tolerant mesenchymal stem cell in patients with chronic stroke and substantial functional deficits was safe and suggested behavioral gains. These data support proceeding to a randomized, placebo-controlled study of this therapy in this population. Clinical Trial Registration- URL: https://www.clinicaltrials.gov. Unique identifier: NCT01297413.